A comprehensive study on the impact of Ligustrum vicaryi L. fruit polysaccharide on myocardial fibrosis through animal experiments, network pharmacology and molecular docking - Liu, Shuling; Liu, Meifang; Wang, Jianan; Rong, Ruixue; Gao, Yanwei; Li, Xiaoqi; Liu, Xin; Li, Shaojian (Frontiers in Cardiovascular Medicine, 2025)
BackgroundMyocardial fibrosis (MF) is a prevalent pathological condition associated with various heart diseases, such as heart failure and arrhythmias, which disrupt electrical signals and reduce pumping efficiency. This research explored the therapeutic effects and potential mechanisms of Ligustrum vicaryi L. fruit polysaccharide (LVFP) on MF.MethodsIn vivo experiments, including fibrosis markers assay, echocardiography, HE staining, Sirius red staining, and Masson's trichrome staining, were performed to evaluate the therapeutic efficacy of LVFP in treating isoproterenol (ISO)-induced MF. We utilized the PharmMapper database to identify targets of LVFP, aiming to explore potential targets. Additionally, we obtained MF-related targets from the GeneCards database. We utilized Venny, a bioinformatics tool, to identify the intersection between the targets of LVFP and those related to MF. We utilized the STRING database to construct a protein interaction network for the overlapping targets and identified key targets for LVFP in treating MF through cytoHubba analysis. We conducted Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis on the intersection targets. We also examined the interaction between LVFP and the key targets using molecular docking techniques.ResultsLVFP significantly inhibited fibrosis biomarker such as hydroxyproline (HYP) and decreased myocardial fibrosis level as shown by heart weight to tibia length (HW/TL) measurement when compared to ISO-treated mice. Additionally, it increased ejection fraction (EF) and fractional shortening (FS) levels. LVFP showed decreased collagen levels compared to the ISO-treated mice by histological quantification of cardiac fibrosis. Based on the monosaccharide structures of LVFP, 413 targets were identified, with 67 associated with MF. Analysis indicated that the 9 hub genes (AKT1, HSP90AA1, SRC, GSK3β, VEGFR2, RHOA, ENO1, PKM, and IL-2) play roles in MF treatment by participating in signaling pathways related to prostate cancer, lipid and atherosclerosis, and insulin resistance. Molecular docking results showed that LVFP exhibited strong binding potential to VEGFR2 (−8.65 kcal/mol), AKT1 (−7.36 kcal/mol) and GSK3β (−7.68 kcal/mol).ConclusionLVFP shows promise as a therapeutic agent for MF, primarily through the regulation of various signaling pathways and targets. These findings provide novel insights for the treatment of MF utilizing LVFP.